A Comparative Study on the Status of Elderly In the Traditional and Modern Societies - Mohammad Esmaeil Riahi (Sālmand, 2008)
Over the past two centuries, the rapid socio-economic transformations along with substantial advances in medicine have resulted in decrease of mortality rate, the significant increase of life expectancy, and the growth of the population aging. In despite of the increased proportion of elderly in the recent periods, their status has significantly decreased. Elderly in the traditional societies had high levels of mastery and authority, especially power, wealth, and prestige. In the light of these assets, they were able to play the vital role in both family and society. However, experiencing rapid changes in the society and family at the present time, the status of elderly is no longer as high as before. The falling trend of elderly's status in the modem societies has resulted in the formation of such stereotypes as elder are not able to take part actively in society. It is important to find exact responses to such questions as whether elderly are useless? and how society can profit their potential and actual abilities? In this regard, the first step is the investigation about roots of decreasing status of old people in the modem world. Overall, the literature review shows that the followings are amongst the most important factors affecting the status of elderly in the modem societies: the decreasing importance of traditional values to control social interaction, the increasing role of mass media and new forms of information technologies to transfer knowledge and science, the decreasing demand to elderly' participation in economic activities, the substantial decreasing in the family size and the emergence of nuclear family, the decreasing responsibilities and duties of family as a social institution, the increasing trend of women employment, the increasing generational gap, the increasing value of youth and beauty, and changing the architecture of residences. Since aging is a multidimensional phenomenon, every effort to empowerment of elderly and increasing their status is necessitated to coordinate and cooperate of all social, economic, political, legal, and medical institutions.